An analysis of three levels of scaled-up coverage for 28 interventions to avert stillbirths and maternal, newborn and child mortality in 27 countries in Latin America and the Caribbean with the Lives Saved Tool (LiST). (December 2016) - Arnesen, Lauren; O'Connell, Thomas; Brumana, Luisa; Durán, Pablo
Abstract Background Action to avert maternal and child mortality was propelled by the Millennium Development Goals (MDGs) in 2000. The Latin American and Caribbean (LAC) region has shown promise in achieving the MDGs in many countries, but preventable maternal, neonatal and child mortality persist. Furthermore, preventable stillbirths are occurring in large numbers in the region. While an effective set of maternal, newborn and child health (MNCH) interventions have been identified, they have not been brought to scale across LAC. Methods Baseline data for select MNCH interventions for 27 LAC countries that are included in the Lives Saved Tool (LiST) were verified and updated with survey data. Three LiST projections were built for each country: baseline, MDG-focused, and All Included, each scaling up a progressively larger set of interventions for 2015 - 2030. Impact was assessed for 2015 - 2035, comparing annual and total lives saved, as projected by LiST. Results Across the 27 countries 235, 532 stillbirths, and 752, 588 neonatal, 959, 393 under-five, and 60, 858 maternal deaths would be averted between 2015 and 2035 by implementing the All-Included intervention package, representing 67 %, 616 %, 807 % and 101 % more lives saved, respectively, than with the MDG-focused interventions. 25 % neonatal deaths averted with the All-Included intervention package would be due to asphyxia, 42 % from prematurity and 24 % from sepsis. Conclusions Our modelling suggests a 337 % increase in the number of lives saved, which would have enormous impacts on population health. Further research could help clarify the impacts of a comprehensive scale-up of the full range of essential MNCH interventions we have modelled.